(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article deals with the structure of urbanonims. It focuses on structural organization of urbanonims of Kriviy Rih. Simple, complex and compound names are distinguished.